First Order for some. How Different Forms of Politicization Motivated Voters in the 2019 European Parliamentary Election. (11th July 2022) - Alt, Dorian; Brandes, Erik; Nonhoff, David
Abstract: Different theories of politicization in EP elections entail very different conclusions for EU legitimacy. The somber predictions of second‐order election (SOE) theory have been challenged by theories of polity politicization in recent years, but many scholars still believe policy politicization to be most desirable from a normative point of view. Despite its importance, there are few studies investigating the meaning citizens attach to their voting decision, which is crucial for disentangling different forms of politicization. We address this gap by choosing a qualitative and explorative research design, conducting 107 semi‐structured interviews in France, Germany and Poland on the day of the 2019 EP elections. Our analysis of voter motivations provides evidence of SOE behavior, but also of European‐level polity and policy politicization. The fact that voters are motivated by different forms of politicization challenges the hegemony of SOE theory. For some voters, EP elections are first order. This is good news for EP legitimacy.